Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis